EVALUASI KINERJA SIMPANG BUNDARAN SOEDARTO DAN USULAN ALTERNATIF PEMECAHANNYA - Priscillia Wanodya Sulistya; Rachma Nurrianti; Bambang Pudjianto; Amelia Kusuma Indriastuti (Jurnal Karya Teknik Sipil, 2014)
Soedarto Roundabout is an icon of Engineering Faculty Complex in Diponegoro University. Tis roundabout becomes a potential location for traffic violations, as it is shifted from the existing junction. Some travellers use it as a shortcut route therefore the traffic performance decrease. Thus, it is necessary to design some alternatives to increase the performance and traffic order. This study aims to identify the traffic characteristics in roundabout area, design some alternatives of intersection management, and determine the best alternative proposal. The quantitative method used in performance analysis of roundabout and the surrounding road network is based on Indonesian Highway Capacity Manual (MKJI, 1997). The qualitative method used is the Analytic Hierarchy Process (AHP) Method. The result shows that traffic order level in this area is quite low, due to many violations caused by the shortcut movements. The number of violation increase in off-peak time. The Degree of Saturation value (DS) of Soedarto Roundabout is 0.88, and the DS of Peternakan Intersection is 0,93. Three alternatives of intersection management in Soedarto Roundabout Area are the change of roundabout and median geometric into priority intersection, chanelization, and roundabout blocking. The quantitative analysis shows that the performance of the third alternative is quite good, with the DS of weaving area between Soedarto Roundabout and Peternakan Junction is 0.70, and the DS of Peternakan Junction is 0.83 (after extended). Thus, the qualitative analysis using AHP shows that the third alternative is the best.